Wettability of amorphous and nanocrystalline Fe78B13Si9 substrates by molten Sn and Bi - Qi Yan; Shen Ping; Sun JianXin; Yang Jun; Jiang QiChuan (Nanoscale Research Letters, 2011)
Abstract The wettability of amorphous and annealing-induced nanocrystalline Fe78B13Si9 ribbons by molten Sn and Bi at 600 K was measured using an improved sessile drop method. The results demonstrate that the structural relaxation and crystallization in the amorphous substrates do not substantially change the wettability with molten Bi because of their invariable physical interaction, but remarkably deteriorate the wettability and interfacial bonding with molten Sn as a result of changing a chemical interaction to a physical one for the atoms at the interface.